Enhancing Learning Outcomes in Science Subjects through Demonstration Method for Fifth Grade at Inpres Seringgu Elementary School - Toding, Diana Arrang; Wibowo, Setiawan Edi; Bafirman, Bafirman (STKIP Singkawang, 2024)
The teaching of science for fifth-grade students at Inpres Seringgu Elementary School, Merauke Regency is mostly teacher-centered, resulting in students’ inadequate comprehension and retention of the subject matter. This study aims to enhance science learning outcomes regarding Earth and the universe through a demonstrative methodology. This research was executed in two iterative cycles concentrating on the primary element of the hydrological cycle. Comprehension of the water cycle idea markedly enhanced student learning outcomes, evidenced by a rise in group success from 43.33% in cycle I to 83.66% in cycle II. Comprehending the water cycle model can enhance student involvement in scientific teaching for fifth-grade pupils at Inpres Seringgu Elementary School, Merauke Regency during the 2023/2024 academic year. The utilization of the water cycle model in knowledge acquisition is more efficacious for comprehending the concept of water in scientific education. This may boost students' creativity in developing and presenting water cycle models, hence increasing participation during teacher explanations and encouraging active learning. The observational data clearly demonstrate that learning outcomes have enhanced between cycles I and II